The consequences of information institutional implications of technological change - Kallinikos, Jannis (Edward Elgar, 2006)
Organizations, information, networks -- Technology design and social systems -- Information growth as a self-referential process -- Excursus on meaning, purpose, and information -- Networks revisited -- Addendum on networks and institutions -- The organizational order of modernity -- Epilogue on technology and institutions
Includes bibliographical references and index
Keywords: Electronic books; Information technology -- Management; Business enterprises -- Computer networks